Cardiovascular Changes Depending on Exercising: Strength Exercise or Nordic Walking (Baltic Journal of Sport and Health Sciences, 2015)
Background. The aim of the study was to compare the acute training effect on the cardiovascular changes under influence of different kinds of health enhancing exercising.Methods. Ten healthy males carried out two health promotion sessions by applying strength type exercising or Nordic-walk. Cardiovascular functional state was assessed before the training session and 30 minutes after the health promotion session by continuous 12-lead ECG recording while performing a Roufier Test (30 squats per 45 s) and by measuring arterial blood pressure.Results. A significant increase in the heart rate at rest was registered after the training session both after the gym training and after Nordic-walking session and reduced diastolic blood pressure values were recorded at rest and after the exercise stress test. If prior to the exercise sessions transient ischemic episode in some subjects was registered, after the training sessions the ischemic episodes were less expressed.Conclusion. Comparing the Nordic walking exercise effects with the effects of strength training exercising during the training session, less increased heart rate and systolic blood pressure were observed; a significantly higher decrease in the diastolic blood pressure, and a significantly lower degree on the short-term effects of functional ischemic myocardium were recorded.Keywords: Nordic walking, strength exercise, cardiovascular system.